Impact of seasonal flooding and hydrological connectivity loss on microbial community dynamics in mangrove sediments of the southern Gulf of Mexico - Vázquez-Rosas-Landa, Mirna; Pérez-Ceballos, Rosela; Zaldívar-Jiménez, Arturo; Hereira, Stephanie; Pérez González, Leonardo; Prieto-Davó, Alejandra; Celis-Hernández, Omar; Canales-Delgadillo, Julio Cesar (PeerJ, 2025)
Background Mangrove ecosystems play essential roles in coastal resilience, carbon sequestration, and biodiversity but are under increasing threat from anthropogenic pressures. This study explores the impact of hydrological variability on microbial communities in mangrove sediments of the southern Gulf of Mexico. Methods We employed 16S rRNA sequencing to assess microbial diversity and function across different hydrological zones, seasons, and sediment depths at Estero Pargo. Results Our results show that microbial community composition is significantly influenced by hydrological conditions, with distinct microbial assemblages observed across the fringe, basin, and impaired zones. Seasonal variations were particularly pronounced, with higher microbial diversity during the flood season compared to the dry season. Depth also played a critical role, with surface layers (5 cm) predominantly featuring aerobic microbial communities, while deeper layers (20–40 cm) harbored anaerobic taxa such as Bathyarchaeota and Thermococcaceae. Notably, the impaired zone showed enrichment in genes related to denitrification and sulfur oxidation pathways, indicating strong microbial adaptation to reduced environments. These findings highlight the intricate interactions between microbial dynamics and environmental factors in mangrove ecosystems. Understanding these relationships is crucial for developing effective conservation and management strategies that enhance mangrove resilience in the face of global environmental changes.
Keywords: Soil; Degradation; Microbiome; Holobiont; Hydroperiod